TrkB signaling is correlated with muscular fatigue resistance and less vulnerability to neurodegeneration - Just-Borràs, Laia; Cilleros-Mañé, Víctor; Polishchuk, Aleksandra; Balanyà-Segura, Marta; Tomàs, Marta; Garcia, Neus; Tomàs, Josep; Lanuza, Maria A. (Frontiers in Molecular Neuroscience, 2022)
At the neuromuscular junction (NMJ), motor neurons and myocytes maintain a bidirectional communication that guarantees adequate functionality. Thus, motor neurons’ firing pattern, which is influenced by retrograde muscle-derived neurotrophic factors, modulates myocyte contractibility. Myocytes can be fast-twitch fibers and become easily fatigued or slow-twitch fibers and resistant to fatigue. Extraocular muscles (EOM) show mixed properties that guarantee fast contraction speed and resistance to fatigue and the degeneration caused by Amyotrophic lateral sclerosis (ALS) disease. The TrkB signaling is an activity-dependent pathway implicated in the NMJ well-functioning. Therefore, it could mediate the differences between fast and slow myocytes’ resistance to fatigue. The present study elucidates a specific protein expression profile concerning the TrkB signaling that correlates with higher resistance to fatigue and better neuroprotective capacity through time. The results unveil that Extra-ocular muscles (EOM) express lower levels of NT-4 that extend TrkB signaling, differential PKC expression, and a higher abundance of phosphorylated synaptic proteins that correlate with continuous neurotransmission requirements. Furthermore, common molecular features between EOM and slow soleus muscles including higher neurotrophic consumption and classic and novel PKC isoforms balance correlate with better preservation of these two muscles in ALS. Altogether, higher resistance of Soleus and EOM to fatigue and ALS seems to be associated with specific protein levels concerning the TrkB neurotrophic signaling.